2001
DOI: 10.1038/sj.bjp.0703943
|View full text |Cite
|
Sign up to set email alerts
|

Platelet GPIIb/IIIa binding characteristics of small molecule RGD mimetic: distinct binding profile for Roxifiban

Abstract: A number of non‐peptide orally active RGD mimetic prodrug such as Orbofiban, Sibrafiban, SR121566, Roxifiban and others entered into the clinical evaluation stage. Some of these agents were terminated and some are still in clinical trials. The present study examined the platelet GPIIb/IIIa binding profiles for the active form of Roxifiban, Sibrafiban, SR121566 and Orbofiban using 3H‐Roxifiban active form (XV459), 3H‐DMP728, 125I‐Echistatin, and 125I‐Fibrinogen. Either DMP728, Orbofiban, Sibrafiban, SR121566 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…[21][22][23][24][25][26] These mutational studies have yielded a great deal of information about platelet function, as specific sequences of these primary functional molecules are being studied as targets for therapeutic approaches. 33 FAK is widely regarded as an integral component of platelet signaling that leads to platelet spreading. 11,32 Integrin engagement with their respective ligands initiates integrin clustering.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] These mutational studies have yielded a great deal of information about platelet function, as specific sequences of these primary functional molecules are being studied as targets for therapeutic approaches. 33 FAK is widely regarded as an integral component of platelet signaling that leads to platelet spreading. 11,32 Integrin engagement with their respective ligands initiates integrin clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Here phage display appears to have selected an interface peptide sequence from the other binding partner in the interaction which, nevertheless, inhibited the interaction. Support for this concept came from the fact that the integrin β3 chain contained a KDDLW sequence, and phage display produced a C WDDGWL C receptor interface peptide sequence which bound to fibronectin or RGD-containing fibronectin fragments [55]. Such peptides inhibited RGD-dependent cell attachment to fibronectin and vitronectin, but not to collagen.…”
Section: H Other Peptide Sequences Related To Rgdmentioning
confidence: 97%
“…32,33 A trivial explanation for this finding would be that abciximab and 7E3 dislodge drug from its binding site. However, abciximab has been shown not to compete with low-molecular-weight RGD-mimetic inhibitors for binding to the integrin 42 or to displace bound inhibitor. 43 Moreover, we found that RGD peptide induces the epitopes recognized by LIBS mAbs PMI-1, LIBS6, 319.1, 322.5, and AP5 even when abciximab is bound to the integrin (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article).…”
Section: Discussionmentioning
confidence: 99%